Beyond the paycheck: Exploring the impact of compensation and benefits on employee retention - Devi, Sharmila; Narayanan, Maran A/L N A; Sagadavan, Revathi; Iddagoda, Anuradha; Lavanya, Latha (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the role of pay and benefits in retaining employees, particularly in the context of strategically applied Human Resource Management (HRM) practices. The research investigates different compensation structures and benefits packing while considering HR experts interviews on the impact of those on retention. These findings highlight the significance of competitive pay and full benefits when it comes to attracting andkeeping the best talent. These include market benchmarking, performance incentives, and transparency around compensation practices. It also examines obstacles including the tension between controlling costs and remaining competitive along with internal pay equity. Companies can create happier employees and a lower turnover rate while promoting a healthy, high-performance culture when they use a data-driven approach and align their HRM practices with higher org goals. The research brings home the message that if companies are to survive in such an ever-changing business environment, they need to have effective systems in place to manage their compensation and benefits programs to maintain their competitive edge. They are important to the long term success of the organization by improving employee loyalty and engagement. Thus, this research adds to the understanding of HRM practices necessary to maximize employee retention and support a high-performing and effective workforce.